The impact of main Areca Catechu root exudates on soil microbial community structure and function in coffee plantation soils - Zhao, Shaoguan; Zhang, Ang; Zhao, Qingyun; Dong, Yunping; Su, Lanxi; Sun, Yan; Zhu, Feifei; Hua, Dangling; Xiong, Wu (Frontiers in Microbiology, 2023)
Coffee is an important cash crop worldwide, but it has been plagued by serious continuous planting obstacles. Intercropping with Areca catechu could alleviate the continuous planting obstacle of coffee due to the diverse root secretions of Areca catechu. However, the mechanism of Areca catechu root secretion in alleviating coffee continuous planting obstacle is still unclear. The changes of coffee rhizosphere soil microbial compositions and functions were explored by adding simulated root secretions of Areca catechu, the primary intercropping plant species (i.e. amino acids, plant hormone, organic acids, phenolic acids, flavonoids and sugars) in current study.The results showed that the addition of coffee root exudates altered soil physicochemical properties, with significantly increasing the availability of potassium and organic matter contents as well as promoting soil enzyme activity. However, the addition of plant hormone, organic acids, or phenolic acids led to a decrease in the Shannon index of bacterial communities in continuously planted coffee rhizosphere soil (RS-CP). The inclusion of phenolic acids specifically caused the decreaseof fungal Shannon index. Plant hormone, flavonoids, phenolic acids, and sugars increased the relative abundance of beneficial bacteria with reduced bacterial pathogens. Flavonoids and organic acids increased the relative abundance of potential fungal pathogen Fusarium. The polyphenol oxidase, dehydrogenase, urease, catalase, and pH were highly linked with bacterial community structure. Moreover, catalase, pH, and soil-available potassium were the main determinants of fungal communities.In conclusion, this study highlight that the addition of plant hormone, phenolic acids, and sugars could enhance enzyme activity, and promote synergistic interactions among microorganisms by enhancing the physicochemical properties of RS-CP, maintaining the soil functions in coffee continuous planting soil, which contribute to alleviate the obstacles associated with continuous coffee cultivation.